A novel turn-on Schiff-base fluorescent sensor for aluminum(iii) ions in living cells. Issue 129 (16th December 2015) - Tian, Jianfei; Yan, Xiaxia; Yang, Hui; Tian, Fuli
Abstract : Quinoline Schiff baseL exhibits a more than 38-fold fluorescence enhancement after addition of Al 3+ ions at an excitation wavelength of 373 nm, and shows a high selectivity for Al 3+ over other metal ions. Abstract : ( E )-4-Methoxy- N -((8-methylquionline-2yl)methylene)aniline (L ) was successfully synthesized and characterized. The complexation behavior ofL with different metal ions was studied using UV-Vis absorption spectroscopy and fluorescence spectroscopy. Results showed that the sensor (L ) exhibited a 38-fold enhancement in fluorescence at 517 nm after adding 10 equiv. of Al 3+ ions. Such fluorescent responses could be detected by the naked eye under a UV-lamp at 365 nm. The complex solution (L –Al 3+ ) showed reversibility with EDTA and the complex was a 1 : 1 ratio according to Job's plot and electrospray ionization mass spectroscopy (ESI-MS). A photoinduced electron transfer (PET) mechanism was considered to be operational for fluorescence enhancement. The detection limit of Al 3+ was calculated to be 1.2 × 10 −7 M, a satisfying level to detect Al 3+ in the micromolar scale. Importantly, the chemosensorL could be used to detect and quantify Al 3+ in living cells. Therefore, this sensor has the ability to be a practical system for monitoring Al 3+ concentrations in biological systems.